Label-free spatio-temporal monitoring of cytosolic mass, osmolarity, and volume in living cells - Daniel Midtvedt (Nature Portfolio, 2019)
Label-free, spatio-temporal imaging of cellular physiological responses is challenging. Here the authors combine digital holographic microscopy with a millifluidic chip and mathematical modelling to quantify cell volume, mass and cell uptake under changing environmental conditions.